Sensing the impact of COVID-19 restrictions from online reviews: The cases of London and Paris unveiled through text mining - Silva, Bruno Rafael Martins da (2022)
This study aims to understand how the COVID-19 pandemic affected the hotel sector and to identify the current traveler demands. The traveler’s reviews were analyzed based on a sentiment and guest satisfaction analysis, demonstrating a data mining approach within tourism and hospitality research. Given its popularity, TripAdvisor was the chosen platform for collection of hotel reviews in London and Paris. The data collection consisted in a dataset of 8k reviews from 226 hotels in total. Text data were extracted from reviews made in two time periods, before and during the COVID-19 pandemic. The sentiment and specific aspects highlighted by travelers were compared between each period. This analysis may also serve as a basis for other studies aimed at a better understanding of the behavior of hotel guests during the COVID-19 pandemic.